Сравнительная характеристика белкового спектра гемолимфы некоторых видов группы Lymnaea Lагnаrk, 1799 (Gastropoda, Pulmonata) - Стадниченко, А.П. (Вестник зоологии, 1974)
Protein spectrum of haemolymph in Lymnaea stagnalis, L. auricularia and L. peregra was studied by means of electrophoresis in agar gel. Statistically trustworthy differences in percentage content of certain protein fractions were established between L. stag- nalis and L. auricularia, L. stagnalis and L. jeregra, as well as between L. auricularia and L. peregra.